'It's a tradition to go down to the pokies on your 18th birthday' – the normalisation of gambling for young women in Australia. (21st September 2020) - McCarthy, Simone; Thomas, Samantha; Pitt, Hannah; Daube, Mike; Cassidy, Rebecca
Abstract: Objective : To understand the range of factors that may influence the normalisation of gambling for young women in Victoria, Australia. Methods : In‐depth qualitative telephone interviews with 45 women aged 18–34 years. Results : Young women were exposed to gambling environments and some were gambling from an early age. Family members were the key facilitators of these activities. Once reaching the legal age of gambling, peers and boyfriends were instrumental in young women's gambling practices. Women attributed the normalisation of gambling to excessive marketing, feminised gambling environments, and the widespread availability of gambling in the community. Conclusions : This study found several factors that influenced and encouraged young women to gamble, such as the feminisation of gambling products and environments, and determined that gambling is becoming a socio‐culturally accepted activity for young women. Implications for public health : Researchers and policymakers should be increasingly focused on how different forms of gambling may be normalised for young women. Attention should be given to how young women may become a target market for the gambling industry, and how to implement strategies aimed at preventing any future potential harm posed by these industries and their marketing tactics and products.